Application of Supportive Therapy Group for Mental-Emotional Problems of Adolescents - Suni, Arsad; Muhammad, Ramli; Muhammad, Al Azhar; Husen, Marti; Tololiu, Tinneke A; Pesak, Ellen (Jurnal Kesehatan, 2025)
Indonesia National Adolescent Mental Health Survey (I-NAMHS) shows that one in three adolescents aged 10-17 years in Indonesia had mental health problems in the last 12 months, equivalent to 15.5 million adolescents in the country and one in 20 adolescents aged 10-17 years in Indonesia also experience mental disorders equivalent to 2.45 million adolescents in the country. Of the 120 respondents, it was found that there were several emotional and mental problems, namely, the aspect of emotional problems in the high abnormal category. This study aims to determine the effect of implementing supportive therapy on adolescent mental problems. This study employs a quantitative, quasi-experimental pre-post-test design with a control group. The inclusion criteria are divided into class A and class B. The total sample used based on the screening results is 120 adolescents. 60 adolescents from class A were given the intervention group, and 60 adolescents from class B were made the control group and did not receive group supportive therapy. The sampling technique used in this study was the total sampling technique. The instrument used was the Strengths and Difficulties Questionnaire (SDQ). The results of the study obtained a range of mental and emotional problems of adolescents in the intervention group before therapy, namely emotional problems 48.3%, behavioral problems 26.7%, peer problems 12.5%, and hyperactivity 12.5%. after therapy, emotional problems were 45%, behavioral problems 16.6%, hyperactivity 3.33%, and peer problems 13.3%. This shows that there is a significant difference between the range of mental and emotional problems after being given supportive group therapy.